Fish consumption pattern among adults of different ethnics in Peninsular Malaysia - Ahmad, Nurul Izzah (Food Nutr Res, 2016)
BACKGROUND: Understanding different patterns of fish consumption is an important component for risk assessment of contaminants in fish. A few studies on food consumption had been conducted in Malaysia, but none of them focused specifically on fish consumption. The objectives of this study were to document the meal pattern among three major ethnics in Malaysia with respect to fish/seafood consumption, identify most frequently consumed fish and cooking method, and examine the influence of demographic factors on pattern of fish consumption among study subjects. METHODS: A cross-sectional survey was conducted between February 2008 and May 2009 to investigate patterns of fish consumption among Malaysian adults in Peninsular Malaysia. Adults aged 18 years and above were randomly selected and fish consumption data were collected using a 3-day prospective food diary. RESULTS: A total of 2,675 subjects, comprising male (44.2%) and female (55.7%) participants from major ethnics (Malays, 76.9%; Chinese, 14.7%; Indians, 8.3%) with a mean age of 43.4±16.2 years, were involved in this study. The results revealed 10 most frequently consumed marine fish in descending order: Indian mackerel, anchovy, yellowtail and yellow-stripe scads, tuna, sardines, torpedo scad, Indian and short-fin scads, pomfret, red snapper, and king mackerel. Prawn and squid were also among the most preferred seafood by study subjects. The most frequently consumed freshwater fish were freshwater catfish and snakehead. The most preferred cooking style by Malaysians was deep-fried fish, followed by fish cooked in thick and/or thin chili gravy, fish curry, and fish cooked with coconut milk mixed with other spices and flavorings. Overall, Malaysians consumed 168 g/day fish, with Malay ethnics’ (175±143 g/day) consumption of fish significantly (p<0.001) higher compared with the other two ethnic groups (Chinese=152±133 g/day, Indians=136±141 g/day). CONCLUSION: Fish consumption was significantly associated with ethnicity, age, marital status, residential area, and years of education of adults in Peninsular Malaysia, and the data collected are beneficial for the purpose of health risk assessment on the intake of contaminants through fish/seafood consumption.